Effect of Betaine on Hepatic and Renal Functions in Acrylamide Treated Rats.: * Ramadhan, Sadiq jaffer and khudair, khalisa khadim - Ramadhan, Sadiq jaffer (The Iraqi Journal of Veterinary Medicine, 2019)
This study was designed to evaluate the ameliorative role of betaine on hepatic and renal dysfunction caused by acrylamide in female rats. Thirty two (32) adult female rats were randomly and equally divided into four groups (G1, G2, G3 and G4) and were treated for (65) days as following: Group G1 (Control group), G2: rats were intubated 250mg/kg B.W of betaine; animals in group G3 were intubated 1mg/kg B.W of acrylamide, in addition to acrylamide. 250mg/kg B.W of betaine were administered orally to rats in groups G4. Fasting (8-12 hrs.) blood samples were collected by cardio puncture technique at the end of the experiment, serum were collected for measuring the following parameters A: liver enzyme makers; serum activity of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP) B; renal function parameters including: serum creatinine, urea and uric acid concentration. The hepato and renal protective effect of betaine was clarified in groups (G2 and G4) manifested by significant decrease in serum, ALT, AST and ALP activity, as well as significant decrease in serum creatinine, urea and uric acid concentration comparing to acrylamide (G3) treated group. Such functional changes were accompanied with structural (histopathological) alteration in hepatic and renal tissue. In conclusion, the results of the current study documented the negative effect of acrylamide on liver and kidney function and documented hepatorenal protective effect of betaine.